Kicking in the guts: Schistosoma mansoni digestive tract proteins are potential candidates for vaccine development - Barbara Castro-Pimentel Figueiredo; Barbara Castro-Pimentel Figueiredo; Natasha Delaqua Ricci; Natasha Delaqua Ricci; Natan Raimundo Gonçalves Assis; Natan Raimundo Gonçalves Assis; Suellen Batistoni Morais; Suellen Batistoni Morais; Cristina Toscano Fonseca; Cristina Toscano Fonseca; Sergio Costa Oliveira; Sergio Costa Oliveira (Frontiers in Immunology, 2015)
Schistosomiasis is a debilitating disease that represents a major health problem in at least 74 tropical and subtropical countries. Current disease control strategies consist mainly of chemotherapy which cannot prevent recurrent re-infection of people living in endemic area. In the last decades, many researchers made a remarkable effort in the search for an effective vaccine to provide long-term protection. Parasitic platyhelminths of Schistosoma genus, which cause the disease, live in the blood vessels of definitive hosts where they are bathed in host blood for many years. Among the most promising molecules as vaccine candidates are the proteins present in the host-parasite interface, so numerous tegument antigens have been assessed and the achieved protection never got even close to 100%. Besides the tegument, the digestive tract is the other major site of host-parasite interface. Since parasites feed on blood, they need to swallow a considerable amount of blood for nutrient acquisition. Host blood ingested by schistosomes passes through the esophagus and reaches the gut where many peptidases catalyze the proteolysis of blood cells. Recent studies show the emergence of antigens related to the parasite blood feeding, such as esophageal gland proteins, proteases and other proteins related to nutrient uptake. Herein, we review what is known about S. mansoni digestive tract proteins, emphasizing the ones described as potential vaccine candidates.